1000 Q&A. (UK : Parragon, 2013)
Want to know why your ears pop? Who invented democracy? Where are boats used as buses? How do we change the world? When did the dinosaurs die out? What is that smell? Get the who? what? where? when? how? and why? on just about everything with 1,000 questions and answers!-- Cover.
Keywords: Science -- Juvenile literature -- Miscellania